2016
DOI: 10.1007/s40789-016-0150-1
|View full text |Cite
|
Sign up to set email alerts
|

Process simulation and analysis of carbon capture with an aqueous mixture of ionic liquid and monoethanolamine solvent

Abstract: This study investigated the prospect of using aqueous mixture of 1-butylpyridinium tetrafluoroborate ([Bpy][BF 4 ]) ionic liquid (IL) and monoethanolamine (MEA) as solvent in post-combustion CO 2 capture (PCC) process. This is done by analysis of the process through modelling and simulation. In literature, reported PCC models with a mixture of IL and MEA solvent were developed using equilibrium-based mass transfer approach. In contrast, the model in this study is developed using rate-based mass transfer approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…These drawbacks of MEA has been addressed through development of new solvents which include mixed amine solvents such as mixtures of MEA and MDEA, AMP and PZ among others (Dubois and Thomas 2012), ammoniabased solvents (Darde et al 2010), amino acid solvent (Brouwer et al 2005), biphasic solvents (Raynal et al 2011) and ionic liquid-based solvents (Boot-Handford et al 2014;Zacchello et al 2016). The new solvents have shown great potential.…”
Section: Solventsmentioning
confidence: 99%
“…These drawbacks of MEA has been addressed through development of new solvents which include mixed amine solvents such as mixtures of MEA and MDEA, AMP and PZ among others (Dubois and Thomas 2012), ammoniabased solvents (Darde et al 2010), amino acid solvent (Brouwer et al 2005), biphasic solvents (Raynal et al 2011) and ionic liquid-based solvents (Boot-Handford et al 2014;Zacchello et al 2016). The new solvents have shown great potential.…”
Section: Solventsmentioning
confidence: 99%
“…Their results showed that [Bpy][BF4]−MEA solvent reduces the heat duty and the capture cost by 15% and 11% respectively compared to reference MEA solvent (i.e., 30 wt% MEA solution). Zacchello et al . presented a rate‐based, solvent‐based capture model for [Bpy][BF4]−MEA hybrid solvent .…”
Section: Introductionmentioning
confidence: 82%
“…Zacchello et al . presented a rate‐based, solvent‐based capture model for [Bpy][BF4]−MEA hybrid solvent . The model was used to investigate the impact of the IL fraction in the mixed solvent on solvent circulation rate and reboiler duty for CO 2 capture from a coke‐oven plant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations